Allocentric vs. Egocentric Spatial Memory Encoding: Evidence for a Cognitive Spatial Map from Virtual Reality Testing - Sévigny, Christophe (My University, 2009)
Navigation is a very important area of spatial information research that presents researchers with a number of challenges. One of these challenges concerns the nature of spatial information encoding itself: is such encoding the result of a single mechanism system, a two-mechanism system or possibly a mixed system? One possible avenue of insight into this problem centers on the disorientation effect as described in Wang & Spelke (2000). A quick survey of basic findings, terminating with Waller & Hodgson (2006), indicates that there seem to be two systems at work. Moreover, the results obtained are based upon experiments carried out in actual reality. A virtual reality experiment was designed in an attempt to replicate the findings described in Waller & Hodgson (2006). The experiment is described in detail and its results are presented. These were found to be sufficiently reliable to justify pointing to a potentially rich field for future research, including such techniques as combining VR with fMRI to achieve more fine-grained results that cannot currently be obtained from the direct use of actual reality only. Underlying factors such as experimental control and data presentation are briefly described in the discussion section.
Keywords: actual reality; allocentric system; egocentric system; geocentric system; hippocampus region; memory encoding mechanism; navigation; place cells; spatial memory encoding; true error; variable error; virtual reality; Psychology; Psychology